Influência das concentrações de açúcares nos mostos sobre o desempenho da fermentação etanólica conduzida em batelada alimentada com vazão variável de alimentação - Gomes, Elenice Mendes Silva (2011)
This study aimed to evaluate the influence of concentrations of sugars in the must, on the performance of ethanol fermentation conducted in fed batch with variable flow of power to define the best concentrations of ART in the must (juice, molasses and mixed) that lead to improved efficiencies and productivity in ethanol fermentation.In the preparation of mash mix were used the following proportions (20% molasses + 80% broth, 40% molasses + 60% broth, 50% molasses + 50% broth, 60% molasses + 40% broth, 80% molasses + 20% broth ). The profile power was declining, varying the flow rate from 0.75 to 0.25 Lh-1, with time filling the fermenter 3 hours for all tests, ranging from 30 to 30 minutes to feed flow wort in fermenter 4L workload (3 liters of wine and 1 liter of inoculum), evaluating diferente concentrations of ART in three types of wine studied. We evaluated performance parameters such as fermentation and process efficiencies and productivity in ethanol. Musts were quantified in pH, sulfuric acid, Brix and ART.In the middle fermented (wine), pH, acidity, residual sugar and ethanol content and quantity of cells. The kinetic profile was defined by quantifying the concentrations of cells, substrate and ethanol (in 1 hour). The figures in this study as a starting point for industrial use are 16 to 18 Brix (ART 114.25 to 125.86 g / L), 16 to 18 ° Brix (ART 127.70 to 141.24 g / L) and around 16 ° Brix (ART 113.68 g / L to 123.30), respectively, for juice of molasses, juice and mix (juice + molasses).The fermentation efficiencies were 77.17 to 90.30% for grape juice, from 74.4 to 86.51% for wine and mixed wine from 61.84 to 84.06 for molasses. Yields were obtained from 6.85 to 8.21 g / Lh for wine broth, 5.90 to 7.77 g / Lh for wine mixed and 4.04 to 6.72 g / Lh for grape molasses. These tracks serve to subsidize recommended as a starting point, the conduct of industrial ethanol fermentation conducted in fed batch with variable flow supply, since the conditions for conducting the tests, as well as the raw materials used in the preparation of musts were similar to those used industrially.